Effects of add-on montelukast on airway hyperresponsiveness in patients with well-controlled asthma – a pilot study. (23rd April 2013) - Kononowa, Nina; Michel, Sandra; Miedinger, David; Pichler, Christiane E.; Chhajed, Prashant N.; Helbling, Arthur; Leuppi, Jörg D.
Abstract: Objective: Control of airway inflammation is the cornerstone of asthma management. The aim of the present pilot study was to assess the effects of a leukotriene receptor antagonist (LTRA) added to a basic treatment of inhaled corticosteroids (ICS) and long-acting beta-agonist (LABA) on airway hyperresponsiveness, inflammation, and quality of life in well-controlled patients with asthma. Research design and methods: Seventeen patients (age 18–65, 11 women) with well-controlled asthma presenting airway hyperresponsiveness to mannitol and methacholine challenge were given add-on montelukast on a stable ICS + LABA for 4 weeks. Quality of life and selected parameters of airway inflammation were measured at baseline and at study end. (ClinicalTrials.gov (NCT01725360)). Results: Adding montelukast to ICS + LABA resulted in an increase in mean FEV1 (+4.5%, p = 0.057), cumulated higher dose of mannitol (+32.5%, p = 0.023) and methacholine (+17.2%, 0.237) in the provocation test, lower airway reactivity with mannitol and methacholine (response dose ratio (RDR) –50.0%, p = 0.024 and –44.3%, p = 0.006, respectively), and improved airway sensitivity to mannitol and methacholine (+12.1%, p = 0.590 and +48.0%, p = 0.129 for PD15 and PD20 FEV1, respectively). Changes in inflammation parameters (blood eosinophil count, serum eosinophil cationic protein, and exhaled nitric oxide) were consistent with these findings. Asthma-related quality of life improved significantly in all domains and overall (from 5.3 at baseline to 6.1 at the final visit, p < 0.001). The main limitation was the absence of a control group. Conclusion: The consistency of the changes in airway hyperresponsiveness and inflammation as well as in quality of life observed with an add-on therapy with montelukast in well-controlled asthma patients during 4 weeks suggests that residual inflammation may represent an area for further improvement of asthma control to be explored in adequately powered randomized controlled trials.